An Analysis of Theories on Stock Returns - Ahmet Sekreter (International Journal of Social Sciences & Educational Studies, 2017)
Objective in writing this article is to provide an overview of the theories that has been developed for stock returns which is an important area of financial markets’ researches. Since the researches in this field are very active for the past quarter, it is not possible to describe all works that has been done in this area. Most important researches will be discussed without going deeper in mathematical tools and theories.